Analysing urban sprawl and land consumption patterns in major capital cities in the Himalayan region using geoinformatics. (December 2017) - Diksha,; Kumar, Amit
Abstract: In the present study, spatio-temporal urban sprawl and land consumption patterns were analysed in seven capital cities located in the Himalayan region during 1972, 1991 and 2015 using multi-temporal satellite images. The study exhibits that capital Himalayan cities experienced rapid growth (830.92%) with high population increase (333.45%) during the observation period (1972–2015). The significant urban growth was observed in the cities of western and middle Himalayan region viz., Srinagar (9.36 km 2 –142.19 km 2 ), Kathmandu (11.38 km 2 –92.58 km 2 ) and Dehradun (4.1 km 2 –50.09 km 2 ) in the higher altitudes due to remarkable increase in the population (0.5–1 million persons) during 1972–2015. On the contrary, Itanagar (7.19 km 2 ), Gangtok (7.09 km 2 ), Shimla (3.04 km 2 ) and Thimphu (2.93 km 2 ) observed less urban growth with moderate to low population growth (i.e., 0.05 to 0.15 million persons). The Shannon entropy based study exhibits that the cities viz., Kathmandu, Gangtok and Itanagar observed comparatively more dispersed urban growth during later period (1991–2015) as compared to the previous period (1972–1991) whereas, the remaining cities observed comparatively less dispersed urban growth during later period. The temporal land consumption pattern exhibits low density urban growth in Srinagar, Dehradun and Kathmandu, as observed with decrease in population density and increasing land consumption during 1972–2015 as compared to other cities, wherein urban densification was evident with increase in population density and decrease in land consumption. The cities in central and western Himalayan region observed high urban growth as compared to cities in eastern Himalayan region. The result shows that the capital cities contributes insignificant proportion (0.5%; 314 km 2 ) of urban area in Himalayan region and accommodating large ( ca . 4 million) population during 2015. The study indicates unplanned and haphazard growth in all capital Himalayan cities, leading towards urban densification as well as dispersion in the periphery with varied pattern and intensity. The specific trends and patterns of urban and population growth are governed by geographical as well as socio-economic-political factors at local to regional scale. The high population pressure induced higher risk to the urban residents as well as constrained urban growth over higher vulnerable zones. The study necessitates implementation of suitable urban planning methods considering socio-economic and physico-cultural characteristics of the region. Highlights: 0.5% (132 km 2 ) of urban area accommodate ca. 4 million populations in Himalayas 2015. Western and middle Himalayan cities had high urban and population growth. Eastern Himalayan cities observed less urban and population growth. Haphazard urban growth leads to urban densification and dispersion in the periphery. Urban growth patterns governed by geographical & socio-economic-political factors.